ANALYSIS OF AKIDAH AKHLAK MATERIAL IN MADRASAH - Khairil Makin Huda; Daifur Rahman; Ach Royhan Syahrul M.P; M. Mahbubi (International Journal of Multidisciplinary Reseach, 2025)
This study aims to analyze the Akidah Akhlak material taught in Madrasah Tsanawiyah (MTS) classes VII, VIII, and IX, with a focus on relevance, quality, and implementation in the formation of student character. The research method used is descriptive qualitative, through observation, interviews, and documentation studies in several MTS. The results of the study indicate that the Akidah Akhlak material has a strategic role in instilling Islamic values ​​and noble morals in students. However, there are challenges in its implementation, such as the lack of innovative learning media, time constraints, and differences in student backgrounds. In addition, the learning approach that is still textual and less contextual causes students to have difficulty in understanding and internalizing the values ​​taught. Learning evaluation that emphasizes more on cognitive aspects is also an obstacle in assessing the extent to which students practice the values ​​of faith and morals in their lives. Therefore, a more contextual approach and the use of technology in delivering materials are needed to improve the effectiveness of learning. This research is expected to contribute to the development of a better curriculum and learning strategies for Faith and Morals in madrasas.